Resolution for a Beveridge Sunday in support of the Beveridge Plan - Short, William
1944-02-14 1944 1940s 1 page NEWCASTLE & DISTRICT TRADES COUNCIL ESTABLISHED 1873. General Secretary WM. SHORT. J P. (To whom all communications should be addressed.) 18, BERTRAM CRESCENT, PENDOWER, NEWCASTLE-ON-TYNE, 5. 14th February 1944 Sir Walter Citrine, K.B.E. General Secretary, Trade Union Congress Transport House, Smith Square, London, S.W.1. Dear Sir, I am instructed to submit to you the following resolution passed at the last meeting of the above Trades Council :- "That in order to demonstrate that the whole nation stands united behind the demand that the Beveridge Plan shall become effective, this Council urges the T.U.C. to appoint a date for a Beveridge Sunday, on which nationwide demonstrations should be held in every town and district in the kingdom to demand the full implementation of the Beveridge Plan without further delay, and that invitations be sent to all parties to participate, the platforms at the meetings to be composed without distinction of class, creed or Party". Trusting that this will receive your attention, I am, Yours faithfully, W. Short General Secretary. 292/150.5/5/27